Highly Efficient and Stable Perovskite Solar Cells Based on Monolithically Grained CH3NH3PbI3 Film. Issue 9 (29th December 2016) - Fei, Chengbin; Li, Bo; Zhang, Rong; Fu, Haoyu; Tian, Jianjun; Cao, Guozhong
Abstract : The synthesis and growth of perovskite films with controlled crystallinity and microstructure for highly efficient and stable solar cells is a critical issue. In this work, thiourea is introduced into the CH3 NH3 PbI3 precursor with two‐step sequential ethyl acetate (EA) interfacial processing. This is shown for the first time to grow compact microsized and monolithically grained perovskite films. X‐ray diffraction patterns and infrared spectroscopy are used to prove that thiourea significantly impacts the perovskite crystallinity and morphology by forming the intermediate phase MAI·PbI2 ·SC(NH2 )2 . Afterward, the residual thiourea which coursed charge recombination is completely extracted by the sequential EA processing. The product has improved light harvesting, suppressed defect state, and enhanced charge separation and transport. The sequentially EA processed perovskite solar cells offer an impressive 18.46% power conversion efficiency and excellent stability in ambient air. More importantly, the EA postprocessed perovskite solar cells also have excellent voltage response under ultraweak light (0.05% sun) with promising utility in photodetectors and photoelectric sensors. Abstract : A new perovskite precursor and a two‐step antisolvent processing method are utilized to grow monolithically grained perovskite films. The as‐prepared films have achieved enhanced light absorption, suppressed surface defect level, and accelerated charge separation and transport. The power conversion efficiency of the solar cells reaches 18.46% with much optimized stability, repeatability, and voltage responsibility.